UPAYA PENGEMBANGAN KOMPETENSI WIDYAISWARA DI LEMBAGA ADMINISTRASI NEGARA - Larissa Absharina (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
The Competency Development Efforts of Widyaiswara in National Institute of Public Administration. In order to achieve qualified and professional civil servants, it has to start with improving the quality and professionalism of the trainers, Widyaiswara. On the other hand, Widyaiswara also holds the position as civil servant, therefore Widyaiswara is required to receive competency development in accordance with their duties and positions. National Institute of Public administration (NIPA) is a supervisory agency for Widyaiswara that has the authority to carry out assessments, education and training of Widyaiswara. NIPA also become a role model in developing competencies of Widyaiswara. This study focuses on explaining the competency development of Widyaiswara carried out by the NIPA by looking at the types of competency development of knowledge, skills, and attitudes. The results of this study concluded that the development of knowledge competencies is carried out through training and community of practice, the development of knowledge competencies is carried out through coaching and mentoring, while the development of attitude competencies is carried out through character development.